Unauthorized Access : The Crisis in Online Privacy and Security - Robert Sloan; Richard Warner (CRC Press, 2014)
Going beyond current books on privacy and security, this book proposes specific solutions to public policy issues pertaining to online privacy and security. Requiring no technical or legal expertise, it provides a practical framework to address ethical and legal issues. The authors explore the well-established connection between social norms, privacy, security, and technological structure. They also discuss how rapid technological developments have created novel situations that lack relevant norms and present ways to develop these norms for protecting informational privacy and ensuring sufficient information security.